Efeito do treinamento funcional sobre a aptidão física, capacidade funcional, relatos de dor e qualidade de vida em mulheres idosas: ensaio clínico - Corrêa, Lucimara da Palma (2019)
Introduction: The Physical Exercise Program with Functional Training (PEF-TF) consists of benefiting the practitioner's autonomy. Objective: To verify the effect of PEF-TF on physical fitness, functional capacity and pain reports in elderly women and their association with quality of life. Method: Non-randomized controlled clinical trial, with elderly women aged 30 from Ourinhos, SP, divided into Study Group (SG = 15) and Control Group (CG= 15), approved by the Ethics Committee under protocol nº 2.285.538 and registered in ReBEC (RBR-9kr2jb). The SG underwent twelve weeks of intervention with the PEF-TF. The groups underwent a battery of motor tests called Senior Fitness Test, anthropometric assessment and answered the questionnaires and scales (Sociodemographic Identification, Functional Capacity by the Katz Index and Lawton's Index, Mini Mental State Examination, Quality of Life / SF-36 , Visual Analog Pain Scale and Nordic Osteomuscular Symptoms Questionnaire). Data were submitted to descriptive statistical analysis and absolute and relative frequencies. Results: Samples presented mean age of 64.9 ± 2.7 years (SG) and 64.2 ± 2.2 years (CG), with a BMI of between 30 and 34.9 for both groups considered as obesity grade I. For the physical fitness tests, the SG presented in the pre and post intervention moments, a statistically significant difference for strength of lower limbs (p = 0.01), aerobic capacity (p = 0.00), percentage of fat (0.04) and reduction of pain intensity (p = 0.01). Quality of life showed high scores in the study group. Conclusion: The Physical Exercise Program with Functional Training had beneficial effects on physical fitness, functional capacity, pain reports and quality of life in the elderly.